Influence of CdхHg1-хTe epitaxial layers defects on photo-electric parameters of matrix detector devices - V. V. Arbenina; A. S. Kashuba; Е. V. Permikina (Тонкие химические технологии, 2013)
In spite of the fact that solid solution CdxHg1-xTe is the most sensitive and effective semiconductor material for matrix photodetectors, weak internuclear connection Hg–Cd and high energy диссоциации molecules Tе2 result in formation CdxHg1-xTe epitaxial layers defects in process MBE epitaxial growth of layers which negatively influence on matrix detector device work. The defects and structural imperfections of epitaxial layers essentially worsens uniformity of distribution of photosensitivity of elements and lowers photo-electric parameters of matrix photodetectors. Therefore the problem of CdxHg1-xTe epitaxial layers defectiveness became the basic at manufacturing of matrix photodetectors, in particular, with small (15-20 microns) step of photosensitive elements. Voltage-current characteristics matrix photosensitive elements were investigated. The analysis of the basic components the dark current and the diagram of photo-electric parameters matrix photodetectors were carried out depending on presence structural and large defects in area p-n transition. Influence of defects on the dark current of matrix detector devices was described. It was established correlations between photo-electric defects matrix detector devices and defects heteroepitaxial layers of the solid solutions CdxHg1-xTe on the basis of which photosensitive elements for matrix devices are created.